A Gene for Genetic Background in Zea mays: Fine-Mapping enhancer of teosinte branched1.2 to a YABBY Class Transcription Factor. Issue 4 (1st December 2016) - Yang, Chin Jian; Kursel, Lisa E; Studer, Anthony J; Bartlett, Madelaine E; Whipple, Clinton J; Doebley, John F
Abstract: The effects of an allelic substitution at a gene often depend critically on genetic background, i.e., the genotypes at other genes in the genome. During the domestication of maize from its wild ancestor (teosinte), an allelic substitution at teosinte branched ( tb1 ) caused changes in both plant and ear architecture. The effects of tb1 on phenotype were shown to depend on multiple background loci, including one called enhancer of tb1.2 ( etb1.2 ). We mapped etb1.2 to a YABBY class transcription factor ( ZmYAB2.1 ) and showed that the maize alleles of ZmYAB2.1 are either expressed at a lower level than teosinte alleles or disrupted by insertions in the sequences. tb1 and etb1.2 interact epistatically to control the length of internodes within the maize ear, which affects how densely the kernels are packed on the ear. The interaction effect is also observed at the level of gene expression, with tb1 acting as a repressor of ZmYAB2.1 expression. Curiously, ZmYAB2.1 was previously identified as a candidate gene for another domestication trait in maize, nonshattering ears. Consistent with this proposed role, ZmYAB2.1 is expressed in a narrow band of cells in immature ears that appears to represent a vestigial abscission (shattering) zone. Expression in this band of cells may also underlie the effect on internode elongation. The identification of ZmYAB2.1 as a background factor interacting with tb1 is a first step toward a gene-level understanding of how tb1 and the background within which it works evolved in concert during maize domestication.